Differences in Kinetics and Coordination between Walking Barefoot and Walking in Rocker Bottom Shoes - Klous, Miriam; Engel, Jennie; Altman, Grace; Barfield, William R (Journal of Sports Research, 2015)
Different types of shoe constructions have been developed with an unstable base including rocker bottom shoes (RBS). RBS were developed to mimic barefoot (BF) walking. Studies have compared walking in RBS with walking in conventional shoes (CS) or running in CS with BF running. The purpose of the current study was to compare RBS with BF walking to describe differences in selected kinetic variables and their timing between the two conditions. Three-dimensional ground reaction force (GRF) and kinematic data for the lower extremities were recorded for 13 college age females during gait at self-selected speed. Similar results were observed between BF walking and walking in RBS. However, several of the observed characteristics of RBS walking were similar to characteristics reported in CS walking. Walking in RBS showed greater vertical GRF (loading response) and anterior-posterior GRF (braking force) than BF walking. Earlier transition from deceleration to acceleration phase was observed in RBS condition, and a shorter time between the peak in ankle plantar flexion moment and the push-of-peak of vertical GRF, and acceleration force in anterior-posterior direction, respectively. Results suggest different strategies between the two conditions to prepare for the swing phase of gait.